Synthesis of N‐Containing Heterocyclic Compounds Using Visible‐light Photoredox Catalysis. Issue 1 (11th January 2016) - Zhou, Lei; Lokman Hossain, Mohammad; Xiao, Tiebo
Abstract: Nitrogen heterocycles represent a highly important class of compounds which are widely used in materials science, agrochemistry, and medicinal chemistry. Therefore, there is continuing interest in the development of convenient, efficient, and environmentally benign synthetic methods for the construction of nitrogen containing heterocycles. Due to its natural abundance, ease of use, and promising application in industry, the use of visible light as a driving force for chemical reactions has received considerable attention in the past few years. This account summarizes the synthesis of N ‐heterocycles using visible‐light photoredox catalysis published in the last two years, according to the size and type of the formed N ‐heterocyclic rings. In the context of seminal works of others in this area, a concise summary of the contributions of the authors is also offered. Abstract : Synthesis of N ‐containing heterocyclic compounds using visible‐light photoredox catalysis : Nitrogen heterocycles represent a highly important class of compounds which are widely used in materials science, agrochemistry, and medicinal chemistry. This account summarizes the synthesis of N ‐heterocycles using visible‐light photoredox catalysis published in the last two years, according to the size and type of the formed N ‐heterocyclic rings. In the context of seminal works of others in this area, a concise summary of the contributions of the authors is also offered.